Scaling issues of neutral theory reveal violations of ecological equivalence for dominant Amazonian tree species. (2nd April 2019) - Pos, Edwin; Guevara, Juan Ernesto; Molino, Jean‐François; Sabatier, Daniel; Bánki, Olaf S.; Pitman, Nigel C.A.; Mogollón, Hugo F.; García‐Villacorta, Roosevelt; Neill, David; Phillips, Oliver L.; Cerón, Carlos; Ríos Paredes, Marcos; et al.
Abstract: Neutral models are often used as null models, testing the relative importance of niche versus neutral processes in shaping diversity. Most versions, however, focus only on regional scale predictions and neglect local level contributions. Recently, a new formulation of spatial neutral theory was published showing an incompatibility between regional and local scale fits where especially the number of rare species was dramatically under‐predicted. Using a forward in time semi‐spatially explicit neutral model and a unique large‐scale Amazonian tree inventory data set, we show that neutral theory not only underestimates the number of rare species but also fails in predicting the excessive dominance of species on both regional and local levels. We show that although there are clear relationships between species composition, spatial and environmental distances, there is also a clear differentiation between species able to attain dominance with and without restriction to specific habitats. We conclude therefore that the apparent dominance of these species is real, and that their excessive abundance can be attributed to fitness differences in different ways, a clear violation of the ecological equivalence assumption of neutral theory.